Strength training for children - Graham, J.
The benefits gained by weight training for children include increased strength, increased protection from potential athletic injuries, enhancement in motor unit recruitment, improvement in the firing rate of activated motor units. There are potential risks due to the relative fragility of the osseous growth structures, however, with proper supervision, appropriate technique instruction and exercise prescription, training related injury can be avoided.